Challenges Associated With the Civilian Reintegration of Soldiers With Chronic PTSD: A New Approach Integrating Psychological Resources and Values in Action Reappropriation - Belrose, Célia; Duffaud, Anais M.; Dutheil, Frédéric; Trichereau, Julie; Trousselard, Marion (Frontiers in Psychiatry, 2019)
Background : In view of the psychological changes for an individual suffering from a chronic Posttraumatic Stress Disorder (PTSD), questions are being raised to understand and allow the recovery and to return to work. This is particularly challenging for soldiers with chronic PTSD , often young individuals suffering from moral conflicts . A French military rehabilitation intervention proposes to broaden the relationships between recovery and reintegration by integrating approaches to the field of positive psychology for soldiers with chronic PTSD. The aim of the study was to evaluate (i) the psychological resources which remain sustainable for these patients, (ii) the resources reappropriation dynamics after the military rehabilitation program focusing in values in action (VIA) as character strengths, and (iii) how these resources and their reappropriation facilitate civilian professional reintegration. Method : We conducted a prospective study with 56 soldiers with chronic PTSD. Clinical severity and psychological resources (optimism, mindfulness, well-being, motivation, self-esteem and VIA) were assessed before and after the rehabilitation program. After identification of resources profiles, we analyzed the impact of the program on resources level and success reintegration to civilian job. Results : 3 profiles of soldiers were identified according to the psychological resources. They differed in term of clinical severity (PCL5). The profile exhibiting both the highest level of resources and the lowest clinical severity of the PTSD did not modify its resources after the intervention program compared to the profile characterised by the lowest level of resources and the highest clinical severity of the PTSD. For this last profile, reappropriation in all VIA was the highest. This profile was associated with the higher rate in reintegration success one year after the intervention. Conclusions : This paper proposed to broaden the relationships between recovery and reintegration by integrating approaches of the field of positive psychology for PTSD. VIA appears as an important factor for reintegration. Results highlights the importance to take into account the existing needs and to optimize the modalities of individual, collective and institutional rehabilitation of these patients suffering from PTSD to better understand the dynamics of the recovery process of a chronically suffering individual.